IMPLEMENTASI SADDU DZARIAH DALAM MEMBERIKAN KEAMANAN, PERLINDUNGAN KONSUMEN PADA E-COMMERCE LAZADA DI INDONESIA - Ermi Suryani Harahap; Nurhotia Harahap (Yurisprudentia: Jurnal Hukum Ekonomi, 2022)
According to As-Syatibi saddu dzariah is an act done by someone who previously contained benefits, but ended up being damaged. The results of the implementation of the saddu dzariah methodology in the perspective of Islamic law prohibits transactions from leaving the system available on the Lazada platform because it causes crimes that are difficult to control and can rarely be overcome without harming platform business owners, platform owner users (store owners, expeditions and consumers). Incompatibility of goods out of the e-commerce system occurs via FB, WhatsApp, Instagram and telephone media. In this case, the government responds as technological advances meet the needs of the community, it is very important for e-commers even though many are misused by irresponsible people. The government protects e-commers users by issuing a save harbor policy to protect platform owners. The Safe Harbor Policy system is a government policy that separates the responsibilities of providers of online buying and selling sites with a User Generated Content (UGC) based marketplace concept from sellers who use their services. This policy is strengthened by the Circular Letter of the Minister of Communication and Information Technology No. 5 of 2016 concerning the limitations of the responsibilities of trading platforms and merchants through electronic means in the form of user generated ed content. Security, convenience of safe platform users when shopping follows the system normally. If the transaction is carried out abnormally, it cannot be controlled by the system provided by Lazada. .